Validation of Different Combination of Three Reversing Half-Hitches Alternating Posts (RHAPs) Effects on Arthroscopic Knot Integrity - Chong, Alexander CM.; Prohaska, Daniel J.; Bye, Brian P. (Kansas Journal of Medicine, 2019)
Introduction. With arthroscopic techniques being used, the importanceof knot tying has been examined. Previous literaturehas examined the use of reversing half-hitches on alternatingposts (RHAPs) on knot security. Separately, there has been researchregarding different suture materials commonly used inthe operating room. The specific aim of this study was to validatethe effect of different stacked half-hitch configuration anddifferent braided suture materials on arthroscopic knot integrity.Methods. Three different suture materials tied withfive different RHAPs in arthroscopic knots were compared.A single load-to-failure test was performed andthe mean ultimate clinical failure load was obtained.Results. Significant knot holding strength improvement wasfound when one half-hitch was reversed as compared to baselineknot. When two of the half-hitches were reversed, therewas a greater improvement with all knots having a mean ultimateclinical failure load greater than 150 newtons (N). Comparisonof the suture materials demonstrated a higher meanultimate clinical failure load when Force Fiber® was used andat least one half-hitch was reversed. Knots tied with eitherForce Fiber® or Orthocord® showed 0% chance of knot slippagewhile knots tied with FiberWire® or braided fishing linehad about 10 and 30% knot slippage chances, respectively.Conclusion. A significant effect was observed in regards to bothstacked half-hitch configuration and suture materials used onknot loop and knot security. Caution should be used with tyingthree RHAPs in arthroscopic surgery, particularly witha standard knot pusher and arthroscopic cannulas. The findingsof this study indicated the importance of three RHAPsin performing arthroscopic knot tying and provided evidenceregarding discrepancies of maximum clinical failure loads observedbetween orthopaedic surgeons, thereby leading to bettersurgical outcomes in the future. KS J Med 2017;10(2):35-39.